An Analysis of Catholic Sacrificial Giving Programs in Seattle, Washington - Harris, Joseph Claude (Review of religious research, 1994)
This paper has two parts. In the first we evaluated a sacrificial giving program in Catholic parishes, using a program group and a control group. Over five years, giving in the program group increased faster than in the control group. In the second part we studied one parish in depth for one year, the beginning year of the program. Giving was much higher than was projected based on past trends. The sacrificial giving program has its greatest effect on people already giving at a higher than average rate.